Integrated optimization of charger deployment and fleet scheduling for battery electric buses. (August 2022) - Wang, Yongxing; Liao, Feixiong; Lu, Chaoru
Highlights: An integrated optimization model is developed for BEBs under opportunity charging. Both charger deployment and fleet scheduling are optimized in the proposed model. The system behavior in response to a group influencing factors are explored. The cost-effective advantage of opportunity charging for BEB system is evaluated. Abstract: Battery electric buses (BEBs) are considered effective options for sustainable mobility. Their operational efficiency is significantly influenced by the deployment of charging infrastructure and the scheduling of the bus fleet. In this research, we develop an integrated optimization model for charger deployment and fleet scheduling for BEBs under opportunity charging. The model jointly optimizes the battery nominal capacity, bus fleet size, and charger deployment at bus stops and the central terminal to minimize the total annualized costs. The time-varying characteristics of ridership, dwelling time, and travel time are considered to investigate realistic solutions with opportunity charging supplied by pantograph chargers. A real-life case study conducted in Oslo, Norway is presented to demonstrate the proposed model, and accordingly sensitivity analysis is further carried out to evaluate the system responses to a group of impact factors. The results indicate that BEB purchase costs and energy consumption rate have significant impacts on total annualized costs, and also imply that opportunity charging has a cost-effective advantage, which can save up to 13.38% of total annualized costs as compared to end station charging using the same type of pantograph charger.